2016
DOI: 10.18178/ijlt.2.1.63-66
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in E-Learning: How Do We Keep Learners Motivated in an E-Learning Environment?

Abstract: E-learning provides students with a different opportunity to learn regardless of where they are and when they are available. In e-learning environment, students are able to participate in self-faced and interactive learning that is otherwise impossible. This paper shows that the use of interactive features of e-learning increases the motivation of undergraduate students for the learning process. Internet technologies provide integrated environment for web-based learning tools to support e-learning education. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…This also applies to the fluency of carrying out tasks for students, where if supported by the availability of facilities, smooth networks and support from lecturers in the form of instructions and motivation, students will be faster in carrying out tasks. This is in accordance with the results of the study (El-Seoud et al, 2016) The results showed that lectures in the form of tutorial still most dominantly influenced student satisfaction compared to discussions and assignments. So that when online lectures use various methods, the composition of the longest time must be in the tutorial lecture model, while discussions and assignments are only complementary additions, not the other way around the dominant assignment (Owens & Price, 2010) The effect of the task which is not significant on student satisfaction, shows the task of making students' conditions the same, many or not the tasks of student satisfaction are the same.…”
Section: Implications and Discussionsupporting
confidence: 92%
“…This also applies to the fluency of carrying out tasks for students, where if supported by the availability of facilities, smooth networks and support from lecturers in the form of instructions and motivation, students will be faster in carrying out tasks. This is in accordance with the results of the study (El-Seoud et al, 2016) The results showed that lectures in the form of tutorial still most dominantly influenced student satisfaction compared to discussions and assignments. So that when online lectures use various methods, the composition of the longest time must be in the tutorial lecture model, while discussions and assignments are only complementary additions, not the other way around the dominant assignment (Owens & Price, 2010) The effect of the task which is not significant on student satisfaction, shows the task of making students' conditions the same, many or not the tasks of student satisfaction are the same.…”
Section: Implications and Discussionsupporting
confidence: 92%
“…The results of the research mentioned that the learning system by the method of e-learning is also very significant effect on the motivation of students. According to (El-Seoud et al, 2016) e-learning gives students different opportunities to learn wherever they are and when time is available. There was a significant relationship between Elearning and the motivation of students (Harandi, 2015).…”
Section: Online Learning Can Eliminate Boredommentioning
confidence: 99%
“…However, as all participants but one voiced reducing OE, this study supports the negative affective predictions within this model. Therefore, this nding suggests that online learning through their VLEs was not a motivational experience (despite research that suggests the contrary: e.g., El-Seoud et al, 2016;Harandi, 2015).…”
Section: Discussionmentioning
confidence: 68%